2020
DOI: 10.1037/adb0000557
|View full text |Cite
|
Sign up to set email alerts
|

A web-based episodic specificity and future thinking session modulates delay discounting in cannabis users.

Abstract: Episodic future thinking (EFT), a brief intervention involving mental simulation of positive future events, improves delay discounting (DD) in nicotine and alcohol dependent individuals. This study is the first to assess effects of a single-session, online episodic training (ET) on constructs that might impact cannabis use and cannabis use disorder. A sample of 200 active cannabis users recruited via Amazon Mechanical Turk were randomized to an EFT group (n ϭ 102) or an episodic recent thinking control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 53 publications
1
27
1
4
Order By: Relevance
“…Our findings are congruent with other brief intervention studies that observed improvement in specificity of events among those with Major Depressive Disorder and Schizophrenia ( 6 , 30 ). Of potential importance to the health behavior treatment field, is to determine if ESI can improve engagement in Episodic Future Thinking (EFT), a brief intervention currently being tested for reducing nicotine, alcohol, and cannabis use and improving healthy food choices ( 22 24 , 31 ). Episodic Future Thinking is an intervention that prompts participants to create and imagine positive, personally relevant future events and is thought to be a product of episodic memory processes and the ability to focus on the future ( 18 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are congruent with other brief intervention studies that observed improvement in specificity of events among those with Major Depressive Disorder and Schizophrenia ( 6 , 30 ). Of potential importance to the health behavior treatment field, is to determine if ESI can improve engagement in Episodic Future Thinking (EFT), a brief intervention currently being tested for reducing nicotine, alcohol, and cannabis use and improving healthy food choices ( 22 24 , 31 ). Episodic Future Thinking is an intervention that prompts participants to create and imagine positive, personally relevant future events and is thought to be a product of episodic memory processes and the ability to focus on the future ( 18 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Episodic Future Thinking is an intervention that prompts participants to create and imagine positive, personally relevant future events and is thought to be a product of episodic memory processes and the ability to focus on the future ( 18 , 32 ). Through strengthening episodic memory processes, administering ESI prior to EFT may improve engagement in EFT, thus improving DD and potentially increasing the impact on reductions in cannabis use and other substances ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of these advances and seminal findings, several experimental studies and clinical trials investigated the therapeutic effects of EFT on reducing delay discounting and consequent maladaptive behaviors and reported positive health-related outcomes as a result of engaging in EFT in people with alcohol use disorder, overweight, obese and prediabetic individuals, cigarette smokers, cannabis users, and people with cocaine use disorder (55)(56)(57)(58)(59)(60)(61). Moreover, EFT training for individuals with addictive behaviors is suggested to improve the efficiency of other psychosocial interventions aiming to attain emotional reappraisal and correction (62).…”
Section: Episodic Future Thinking: How Could It Put Extinction Into Practice?mentioning
confidence: 99%
“…EFT involves imagining future events through guided instruction and aims to promote a longer-term mindset 29 . EFT has shown efficacy at improving preference for larger delayed rewards over smaller immediate rewards in substance-using populations 30,31 . The language was updated to target a younger adult population (previously aimed at older adults) and is more aligned with therapeutic and conversational dialogue, rather than educational training language.…”
Section: Preliminary Work On Re-developmentmentioning
confidence: 99%